Exercise recommendation for people with bone metastases: expert consensus for health care providers and exercise professionals - Campbell, Kristin L.; Cormie, Prue; Weller, Sarah; Alibhai, Shabbir M. H.; Bolam, Kate A.; Campbell, Anna; Cheville, Andrea L.; Dalzell, Mary-Ann; Hart, Nicolas H.; Higano, Celestia S.; Lane, Kirstin; Mansfield, Sami; et al. (JCO oncology practice, 2022)
PURPOSE: Exercise has been underutilized in people with advanced or incurable cancer despite the potential to improve physical function and reduce psychosocial morbidity, especially for people with bone metastases because of concerns over skeletal complications. The International Bone Metastases Exercise Working Group (IBMEWG) was formed to develop best practice recommendations for exercise programming for people with bone metastases on the basis of published research, clinical experience, and expert opinion. - METHODS: The IBMEWG undertook sequential steps to inform the recommendations: (1) modified Delphi survey, (2) systematic review, (3) cross-sectional survey to physicians and nurse practitioners, (4) in-person meeting of IBMEWG to review evidence from steps 1-3 to develop draft recommendations, and (5) stakeholder engagement. - RESULTS: Recommendations emerged from the contributing evidence and IBMEWG discussion for pre-exercise screening, exercise testing, exercise prescription, and monitoring of exercise response. Identification of individuals who are potentially at higher risk of exercise-related skeletal complication is a complex interplay of these factors: (1) lesion-related, (2) cancer and cancer treatment-related, and (3) the person-related. Exercise assessment and prescription requires consideration of the location and presentation of bone lesion(s) and should be delivered by qualified exercise professionals with oncology education and exercise prescription experience. Emphasis on postural alignment, controlled movement, and proper technique is essential. - CONCLUSION: Ultimately, the perceived risk of skeletal complications should be weighed against potential health benefits on the basis of consultation between the person, health care team, and exercise professionals. These recommendations provide an initial framework to improve the integration of exercise programming into clinical care for people with bone metastases.